Ответы и объяснения

2013-02-14T17:33:39+04:00

(x2-2x)/(x-1)+(2x-1)/(x-1)=3 | x-1            | x-1 - это умножить

0+2x-1=3

2x-1=3

x=2 

2013-02-14T17:42:51+04:00

х2-2х(дополнительный множитель1-х              2х-1(д.п.х-1   3(д.п.(х-1)(1-х)

-------------------------------------------------------   -     ------------------= -------------------

 

 х-1                                                                                      1-х                          1          

дальше давай сам через Д=вКВ-4ас

у меня нет глючит